Visualization of Airborne Particles as a Risk for Microbial Contamination in Orthopedic Surgery - Koseki, Hironobu; Sunagawa, Shinya; Imai, Chieko; Yonekura, Akihiko; Matsumura, Umi; Yokoo, Seiichi; Watanabe, Kaho; Nishiyama, Yuta; Osaki, Makoto (Frontiers in Surgery, 2021)
Background: The operating theatre is recognized for the high frequency of occupational blood and body fluid contact. Objectives: This study aimed to visualize the production of blood and body fluid airborne particles by surgical procedures and to investigate risks of microbial contamination of the conjunctival membranes of surgical staff during orthopedic operations. Methods: Two physicians simulated total knee arthroplasty (TKA) and total hip arthroplasty (THA) in a bio-clean theatre using model bones. The generation and behaviours of airborne particles were filmed using a fine particle visualization system, and numbers of airborne particles per 2.83 L of air were counted at the height of the operating and instrument tables. Each action was repeated five times, and particle counts were evaluated statistically. Results: Numerous airborne particles were dispersed to higher and wider areas while “cutting bones in TKA” and “striking and driving the cup component on the pelvic bone in THA” compared to other surgical procedures. The highest particle counts were detected while “cutting bones in TKA” under unidirectional laminar air flow. Discussion: These results provide a clearer image of the dispersion and distribution of airborne particles and identified higher-risk surgical procedures for microbial contamination of the conjunctival membranes. Surgical staff including surgeons, nurses, anesthesiologists, and visitors, should pay attention to and take measures against occupational infection particularly in risky surgical situations.